The Effectiveness of Online Circulation Service (SIDARING) in Supporting Services at the Library Unit of Universitas Negeri Padang - Riska Monita Yanti; Marlini Marlini (Darul Yasin Al Sys, 2026)
The effectiveness of digital circulation services in academic libraries has become increasingly important for supporting accessibility, efficiency, and continuity of library services in the post-pandemic era. However, the implementation of digital systems does not automatically ensure optimal service effectiveness, particularly when user needs and service utilization patterns continue to evolve. This study aims to analyze the effectiveness of the Online Circulation Service (Sirkulasi Dalam Jaringan/SIDARING) in supporting services at the Library Unit of Universitas Negeri Padang using the Electronic Service Quality (E-Servqual) framework. A quantitative approach with a descriptive design was employed to obtain an empirical overview of users’ perceptions of SIDARING effectiveness. The study involved 100 respondents selected through simple random sampling from a population of 3,794 SIDARING users. Data were collected using a structured questionnaire consisting of 30 items measured on a four-point Likert scale and analyzed using descriptive statistical techniques. The findings indicate that SIDARING generally operates effectively, as reflected in positive evaluations across six E-Servqual dimensions: efficiency, fulfillment, system availability, privacy, responsiveness, and contact. Privacy and contact obtained the highest evaluations, indicating strong user trust in data security and communication accessibility, while efficiency, fulfillment, system availability, and responsiveness remained in the high category, suggesting adequate service performance in meeting user needs. The study concludes that SIDARING functions effectively as a digital circulation service that improves convenience, accessibility, and service continuity in academic library environments. This study contributes to digital library service evaluation by demonstrating the applicability of the E-Servqual framework in assessing online circulation services, with practical implications for system optimization, communication improvement, technical maintenance, and user-oriented service innovation.